Method for recovering iron phosphate from lithium iron phosphate slurry
By calcining the lithium iron phosphate slurry and the fluorine-containing material in an oxygen atmosphere, the complex problem of recycling iron phosphate in the prior art is solved, and high purity and high yield iron phosphate recovery is achieved, the process flow is simplified, and the avoidance of Resource waste and environmental pollution.
Patent Information
- Application Number
- CN202411168837.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-07
AI Technical Summary
The method of recycling iron phosphate in the prior art is complex, and there are few researches on the recycling of scrapped positive electrode slurry during the preparation of lithium iron phosphate batteries, resulting in waste of resources and environmental pollution.
通过将磷酸铁锂浆料进行烘干处理后与含氟材料混合,并在氧气氛中煅烧处理,利用HF气体破坏磷酸铁锂结构,生成高纯度的磷酸铁。
It achieves high yield and high purity recovery of iron phosphate, simple operation, and is more convenient and effective than other acid-added dissolution and filtration methods.
Smart Images

Figure CN119263236A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a method for recovering iron phosphate from lithium iron phosphate slurry. Background Art
[0002] Lithium iron phosphate is a commonly used positive electrode material for lithium-ion batteries due to its excellent structural stability, cycle performance and safety performance. With the arrival of the lithium battery retirement wave, a large number of retired batteries, battery cells and pole pieces and slurries generated during the battery preparation process need to be recycled. If the recycling is not done properly, it will not only cause certain environmental pollution but also cause a lot of waste of resources.
[0003] As an important component of lithium batteries, lithium iron phosphate batteries have been increasingly studied in recent years. Currently, most researchers dissolve lithium iron phosphate batteries by self-discharging, disassembling them, adding strong acid to dissolve them, and adjusting the pH value to recover iron phosphate, lithium salts or other iron salts. However, there are few studies on directly recycling the scrapped positive electrode slurry in the preparation process of lithium iron phosphate batteries and recovering the iron phosphate in it. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for recovering iron phosphate from lithium iron phosphate slurry, so as to solve the problem that the methods for recovering iron phosphate in the prior art are relatively complicated.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for recovering iron phosphate from lithium iron phosphate slurry is provided, the method comprising the following steps: step S1, drying the lithium iron phosphate slurry to obtain a lithium iron phosphate-containing solid; step S2, mixing and calcining the raw materials including the lithium iron phosphate-containing solid and the fluorine-containing material in sequence to obtain iron phosphate; wherein the calcination is carried out in an oxygen-containing atmosphere.
[0006] Furthermore, in the above step S2, the mass ratio of the lithium iron phosphate solid to the fluorine-containing material is 1:0.8-1.2.
[0007] Furthermore, in the above step S2, the fluorine-containing material is polyvinylidene fluoride and / or polytetrafluoroethylene; preferably, the fluorine-containing material is a combination of polyvinylidene fluoride and polytetrafluoroethylene, and the mass ratio of polyvinylidene fluoride to polytetrafluoroethylene is 1:0.1-0.5.
[0008] Furthermore, in the above step S2, the oxygen content in the oxygen-containing atmosphere is 20% to 100%; and / or, the calcination temperature is 600 to 800° C.; and / or, the calcination time is 2 to 4 hours.
[0009] Furthermore, in the above step S2, the purity of the iron phosphate is 80.2% to 99.6%; and / or the particle size of the iron phosphate is 0.2 to 1 μm.
[0010] Furthermore, in the above step S2, the mixing treatment is dry ball milling, the rotation speed of the dry ball milling is 200 to 500 r / min; and / or the time of the dry ball milling is 2 to 5 h.
[0011] Furthermore, in the above step S1, the temperature of the drying treatment is 100-120° C.; and / or the time of the drying treatment is 4-8 hours.
[0012] Furthermore, the above step S1 also includes crushing the product after the drying process, and the crushing process time is 3 to 10 minutes.
[0013] Furthermore, the lithium iron phosphate slurry comprises lithium iron phosphate, a conductive agent, a binder and an organic solvent.
[0014] Furthermore, the conductive agent is conductive carbon, the binder is polyvinylidene fluoride, the organic solvent is N-methylpyrrolidone, and the mass ratio of lithium iron phosphate, conductive carbon and polyvinylidene fluoride is 90-95:2.5-5:2.5-5.
[0015] Applying the technical solution of the present invention, in step S1, the lithium iron phosphate slurry is dried to remove the organic solvent in the lithium iron phosphate slurry, and in step S2, the lithium iron phosphate solid and the fluorine-containing material are mixed to help the fluorine-containing material be evenly dispersed in the lithium iron phosphate solid, and the mixture is calcined. The fluorine-containing material decomposes under high temperature conditions to produce HF gas, and the generated HF gas destroys the structure of lithium iron phosphate to generate iron phosphate, and the lithium volatilizes as an oxide or fluoride; the carbon element in the mixture reacts with the oxygen in the oxygen-containing atmosphere to generate carbon dioxide gas, and finally prepares iron phosphate with high yield and purity. The operating process of recovering iron phosphate in the present application is simple, and it is more convenient and effective than other methods such as acid dissolution and filtration for recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 shows the XRD pattern of iron phosphate in Example 1 of the present application;
[0018] Figure 2 The SEM image of iron phosphate in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] As analyzed in the background technology of this application, there are relatively complex problems in the methods of recovering iron phosphate in the prior art. In order to solve the above problems, this application provides a method for recovering iron phosphate from lithium iron phosphate slurry.
[0021] In a typical embodiment of the present application, a method for recovering iron phosphate from lithium iron phosphate slurry is provided, the method comprising the following steps: step S1, drying the lithium iron phosphate slurry to obtain a lithium iron phosphate-containing solid; step S2, mixing and calcining the raw materials including the lithium iron phosphate-containing solid and the fluorine-containing material in sequence to obtain iron phosphate; wherein the calcination is carried out in an oxygen-containing atmosphere.
[0022] In step S1, the lithium iron phosphate slurry is dried to remove the organic solvent in the lithium iron phosphate slurry. In step S2, the lithium iron phosphate solid and the fluorine-containing material are mixed to help the fluorine-containing material to be evenly dispersed in the lithium iron phosphate solid. The mixture is calcined, and the fluorine-containing material decomposes under high temperature conditions to produce HF gas. The generated HF gas destroys the structure of lithium iron phosphate and generates iron phosphate, and the lithium volatilizes as an oxide or fluoride; the carbon element in the mixture reacts with the oxygen in the oxygen-containing atmosphere to generate carbon dioxide gas, and finally prepares iron phosphate with high yield and purity. The operating process of recovering iron phosphate in the present application is simple, and it is more convenient and effective than other methods such as acid dissolution and filtration.
[0023] In one embodiment of the present application, in the above step S2, the mass ratio of the lithium iron phosphate solid to the fluorine-containing material is 1:0.8-1.2.
[0024] The mass ratio of the lithium iron phosphate solid and the fluorine-containing material is preferably controlled within the above range, which helps to further remove the lithium element in the lithium iron phosphate solid, thereby helping to further improve the yield and purity of the finally formed iron phosphate.
[0025] In one embodiment of the present application, in the above step S2, the fluorine-containing material is polyvinylidene fluoride and / or polytetrafluoroethylene; preferably, the fluorine-containing material is a combination of polyvinylidene fluoride and polytetrafluoroethylene, and the mass ratio of polyvinylidene fluoride to polytetrafluoroethylene is 1:0.1-0.5.
[0026] It is preferred to control the type of fluorine-containing material within the above range, which helps to further increase the fluorine element in the fluorine-containing material, so that the fluorine-containing compound decomposes at high temperature to produce sufficient HF gas, which more thoroughly destroys the lithium iron phosphate structure and generates iron phosphate, making lithium oxide and lithium fluoride more volatilizable, thereby helping to further improve the yield and purity of the iron phosphate finally formed.
[0027] In one embodiment of the present application, in the above step S2, the oxygen content in the oxygen-containing atmosphere is 20% to 100%; and / or, the calcination temperature is 600 to 800° C.; and / or, the calcination time is 2 to 4 hours.
[0028] It is preferred to control the oxygen content in the oxygen-containing atmosphere within the above range, which helps to further remove the carbon element in the lithium iron phosphate solid, thereby helping to further improve the yield and purity of the iron phosphate. Too high a calcination temperature and too long a calcination time are not conducive to the orderly growth of iron phosphate crystals, and too low a calcination temperature and too short a calcination time are not conducive to the removal of impurities in the iron phosphate. It is preferred to control the calcination temperature and time within the above range, which helps to further improve the yield and purity of the iron phosphate and improve the efficiency of the formation of the iron phosphate.
[0029] In one embodiment of the present application, in the above step S2, the purity of the iron phosphate is 80.2% to 99.6%; and / or the particle size of the iron phosphate is 0.2 to 1 μm.
[0030] The iron phosphate prepared according to the preparation method of the present application has a particle size and purity within the above range, making it more suitable for use as a battery material.
[0031] In order to further improve the uniformity of mixing of lithium iron phosphate solid and fluorine-containing material, in one embodiment of the present application, preferably, in the above step S2, the mixing treatment is dry ball milling, the rotation speed of the dry ball milling is 200 to 500 r / min; and / or the time of the dry ball milling is 2 to 5 h.
[0032] In order to further remove the organic solvent in the lithium iron phosphate slurry, in one embodiment of the present application, preferably, in the above step S1, the drying treatment temperature is 100-120° C.; and / or the drying treatment time is 4-8 hours.
[0033] In order to further increase the contact area between the lithium iron phosphate solid and the fluorine-containing material, in one embodiment of the present application, preferably, the above step S1 also includes crushing the product after the drying treatment, and the crushing time is 3 to 10 minutes.
[0034] It is preferred to control the crushing treatment time within the above range, which helps to further improve the efficiency of the crushing treatment. Furthermore, it is preferred that the average particle size of the lithium iron phosphate solid obtained after the crushing treatment is 1 to 3 μm.
[0035] In one embodiment of the present application, the above-mentioned lithium iron phosphate slurry includes lithium iron phosphate, a conductive agent, a binder and an organic solvent; preferably, the conductive agent is conductive carbon, the binder is polyvinylidene fluoride, the organic solvent is N-methylpyrrolidone, and the mass ratio of lithium iron phosphate, conductive carbon and polyvinylidene fluoride is 90~95:2.5~5:2.5~5.
[0036] The lithium iron phosphate slurry with the above composition is preferably more suitable for recycling with the method of the present application to obtain high-purity and excellent-performance iron phosphate.
[0037] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0038] Example 1
[0039] 20kg of lithium iron phosphate slurry was collected from the lithium iron phosphate coating process of the battery factory. 1.5kg of the collected slurry was weighed and evenly spread on a stainless steel tray (75*40cm). The stainless steel tray was placed in a blast oven for drying, the temperature was controlled at 110℃, circulating air was passed, and the heat was kept for 4 hours. Then the dried material was transferred to a crusher for mechanical crushing for 5 minutes to obtain lithium iron phosphate solid. Lithium iron phosphate solid and polyvinylidene fluoride were weighed at a mass ratio of 1:1, and the weighed materials were mixed evenly by dry ball milling. The speed of dry ball milling was 500r / min, and the time of dry ball milling was 4 hours. The mixed material was transferred to a muffle furnace for calcination, and kept at 700℃ in air atmosphere for 2 hours to obtain iron phosphate.
[0040] Example 2
[0041] The difference from Example 1 is that the total mass of lithium iron phosphate solid and polyvinylidene fluoride remains unchanged, the mass ratio of lithium iron phosphate solid to polyvinylidene fluoride is 1:0.8, and iron phosphate is finally obtained.
[0042] Example 3
[0043] The difference from Example 1 is that the total mass of lithium iron phosphate solid and polyvinylidene fluoride remains unchanged, the mass ratio of lithium iron phosphate solid to polyvinylidene fluoride is 1:1.2, and iron phosphate is finally obtained.
[0044] Example 4
[0045] The difference from Example 1 is that the total mass of lithium iron phosphate solid and polyvinylidene fluoride remains unchanged, the mass ratio of lithium iron phosphate solid to polyvinylidene fluoride is 1:0.75, and iron phosphate is finally obtained.
[0046] Example 5
[0047] The difference from Example 1 is that a composition of polyvinylidene fluoride and polytetrafluoroethylene is used to replace polyvinylidene fluoride, and the mass ratio of polyvinylidene fluoride to polytetrafluoroethylene is 1:0.1, and iron phosphate is finally obtained.
[0048] Example 6
[0049] The difference from Example 1 is that a composition of polyvinylidene fluoride and polytetrafluoroethylene is used to replace polyvinylidene fluoride, and the mass ratio of polyvinylidene fluoride to polytetrafluoroethylene is 1:0.5, and iron phosphate is finally obtained.
[0050] Example 7
[0051] The difference from Example 1 is that the calcination temperature is 800° C., the calcination time is 2 h, and iron phosphate is finally obtained.
[0052] Example 8
[0053] The difference from Example 1 is that the calcination temperature is 600° C., the calcination time is 4 hours, and iron phosphate is finally obtained.
[0054] Example 9
[0055] The difference from Example 1 is that the calcination temperature is 900° C., the calcination time is 1 h, and iron phosphate is finally obtained.
[0056] Example 10
[0057] The difference from Example 1 is that the rotation speed of the dry ball mill is 200 r / min, the time of the dry ball mill is 2 h, the temperature of the drying treatment is 100° C., the time of the drying treatment is 4 h, and the time of the crushing treatment is 3 min, and finally iron phosphate is obtained.
[0058] Embodiment 11
[0059] The difference from Example 1 is that the rotation speed of the dry ball mill is 500 r / min, the time of the dry ball mill is 5 h, the temperature of the drying treatment is 120° C., the time of the drying treatment is 8 h, and the time of the crushing treatment is 10 min, and finally iron phosphate is obtained.
[0060] The iron phosphate prepared in the above example was tested by inductively coupled plasma atomic emission spectrometer (ICP), and the yield and purity of the iron phosphate were calculated and shown in Table 1.
[0061] Table 1
[0062] Example Yield / % purity / % Example 1 92.7 98.5 Example 2 88.3 85.6 Example 3 90.7 86.9 Example 4 85.3 80.2 Example 5 95.3 99.2 Example 6 96.1 99.6 Example 7 91.5 98.9 Example 8 92.6 98.1 Example 9 84.4 81.1 Example 10 92.4 98.2 Embodiment 11 93.8 98.7
[0063] Figure 1 is the XRD pattern of iron phosphate in Example 1, from Figure 1 It can be seen that iron phosphate can well maintain the diffraction peak of iron phosphate, and there are no other impurity peaks, and it has good crystallization properties.
[0064] Figure 2 is the SEM image of iron phosphate in Example 1, from Figure 2 It can be seen that iron phosphate exists in irregular polyhedrons, the size of the polyhedrons is relatively uniform and small, all below 1μm.
[0065] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0066] In step S1, the lithium iron phosphate slurry is dried to remove the organic solvent in the lithium iron phosphate slurry. In step S2, the lithium iron phosphate solid and the fluorine-containing material are mixed to help the fluorine-containing material to be evenly dispersed in the lithium iron phosphate solid. The mixture is calcined, and the fluorine-containing material decomposes under high temperature conditions to produce HF gas. The generated HF gas destroys the structure of lithium iron phosphate and generates iron phosphate, and the lithium volatilizes as an oxide or fluoride; the carbon element in the mixture reacts with the oxygen in the oxygen-containing atmosphere to generate carbon dioxide gas, and finally prepares iron phosphate with high yield and purity. The operating process of recovering iron phosphate in the present application is simple, and it is more convenient and effective than other methods such as acid dissolution and filtration.
[0067] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for recovering iron phosphate from lithium iron phosphate slurry, characterized in that: The method comprises the following steps: Step S1, drying the lithium iron phosphate slurry to obtain a lithium iron phosphate-containing solid; Step S2, mixing and calcining the raw materials including the lithium iron phosphate solid and the fluorine-containing material in sequence to obtain iron phosphate; wherein the calcination is carried out in an oxygen-containing atmosphere.
2. The method according to claim 1, characterized in that: In the step S2, the mass ratio of the lithium iron phosphate solid to the fluorine-containing material is 1:0.8-1.
2.
3. The method according to claim 1 or 2, characterized in that: In the step S2, the fluorine-containing material is polyvinylidene fluoride and / or polytetrafluoroethylene; preferably, the fluorine-containing material is a combination of polyvinylidene fluoride and polytetrafluoroethylene, and the mass ratio of the polyvinylidene fluoride to the polytetrafluoroethylene is 1:0.1-0.
5.
4. The method according to any one of claims 1 to 3, characterized in that In the step S2, the oxygen content in the oxygen-containing atmosphere is 20% to 100%; and / or the calcination temperature is 600 to 800° C.; and / or the calcination time is 2 to 4 hours.
5. The method according to any one of claims 1 to 4, characterized in that In the step S2, the purity of the ferric phosphate is 80.2% to 99.6%; and / or the particle size of the ferric phosphate is 0.2 to 1 μm.
6. The method according to any one of claims 1 to 5, characterized in that In the step S2, the mixing treatment is dry ball milling, the rotation speed of the dry ball milling is 200 to 500 r / min; and / or the time of the dry ball milling is 2 to 5 hours.
7. The method according to any one of claims 1 to 6, characterized in that In the step S1, the temperature of the drying process is 100-120° C.; and / or the time of the drying process is 4-8 hours.
8. The method according to any one of claims 1 to 7, characterized in that The step S1 further comprises crushing the product after the drying process, and the crushing process takes 3 to 10 minutes.
9. The method according to any one of claims 1 to 8, characterized in that The lithium iron phosphate slurry includes lithium iron phosphate, a conductive agent, a binder and an organic solvent.
10. The method according to claim 9, characterized in that The conductive agent is conductive carbon, the binder is polyvinylidene fluoride, the organic solvent is N-methylpyrrolidone, and the mass ratio of the lithium iron phosphate, the conductive carbon and the polyvinylidene fluoride is 90-95:2.5-5:2.5-5.